The role of periprocedural hemodynamic variables during carotid stenting for the mid-term general mortality in advanced age patients - Teodora Yaneva-Sirakova; Galina Zlatancheva; Kiril Karamfiloff; Latchezar Traykov; Ivo Petrov; Dobrin Vassilev (Folia Medica, 2023)
Introduction: Carotid stenting may produce significant bradycardia and/or hypotension. This may have negative short- and long-term effects for the elderly high-risk patients. Their cerebral hemodynamics is with exhausted adaptive capacity because of the multiple cardiovascular risk factors, advanced age, and significant stenosis. Aim: This was a retrospective study aimed at finding whether periprocedural hypoperfusion or hypotension at the time of carotid stenting had any significance for the acute neurological outcome and mid-term general mortality in advanced-age patients who were at high risk for surgical endarterectomy. Materials and methods: We studied 138 consecutive patients with significant carotid stenosis from January 2015 to July 2019. The mean (SD) age was 67.41 (10.70) years. The mean follow-up period was 31 months (922 days). The patients were hemodynamically monitored periprocedurally according to a local protocol. Vasopressors were added if a prolonged hypotension was measured. Statistical data were analyzed using SPSS IBM v. 19 (p=0.05, CI 95%). Results: The male patients were 94 (68%). The number of patients with hypotension periprocedurally or in the first 6 hours post-procedure was 55 (42%). The mean blood pressures were 135/83 mmHg before, 116/76 mmHg during, and 121/73 mmHg after the procedure. Kaplan-Maier analysis showed no significant differences in the mid-term general mortality rate between patients with and patients without transitory hypotension. There wasn’t any difference in the postprocedural neurological outcome either. Conclusions: The presence of hypotension during carotid stenting was not linked to a negative neurological outcome. It also did not increase mid-term all-cause mortality in elderly patients (mean age, 67 years). The finding could be attributed to the relatively brief period of hypotension, the prompt administration of vasopressors, or the prevention of brain edema and hyper-reperfusion during carotid stenting in terms of elevated blood pressure; however, this remains to be determined.